HUBUNGAN KADAR D-DIMER DENGAN AWITAN GEJALA DAN LAMA PERAWATAN PADA PENDERITA CEREBRAL VENOUS SINUS THROMBOSIS DI RSUP DR HASAN SADIKIN BANDUNG - Lisda Amalia; Adnin Nugroho (NEURONA, 2020)
CORRELATION BETWEEN D-DIMER LEVEL WITH ONSET OF SYMPTOMS AND LENGTH OF STAY IN CEREBRAL VENOUS SINUS THROMBOSIS PATIENTS AT HASAN SADIKIN HOSPITAL BANDUNGABSTRACTIntroduction:Cerebral venous sinus thrombosis (CVST)is one of a cerebrovascular disease with a diverse and elusive clinical presentation. Diagnosis is often challenging due to limitation in diagnostic tools.Coagulation disorder is one of the risk factor for CVST that can be seen from D-dimer level which tends to increase in CVST patients.Aim: This study aims to determine the D-dimer leveland its correlation with onset of symptoms and length of stay in CVST patients at Hasan Sadikin Hospital, Bandung.Methods: This is a cross-sectional study. The inclusion criteria were patients at Hasan Sadikin Hospital, Bandung diagnosed as CVST, confirmed by digital subtraction angiography (DSA) or computed tomography angiography (CTA) or magnetic resonance angiography (MRA) and had blood coagulation profile in the period of January 2018-May 2019. Exclusion criteria were patients with infection or sepsis. Data were collected from the patient’s medical record. Statistical value was calculated with Spearman rank test, p value<0.05 was considered significant.Results: Forty CVST patients met the criteria. CVST mostly occurred in women (80%), the mean age were 40,75 years, and had headache as primary symptom (70%). Twenty-eight(70%) patients had increased level of D-dimer. D-dimer level had negative correlation with onset of symptoms (r=-0.319, p=0.045). However, it hadassociationwith length of stay (p=0.012).Discussion: D-dimer level in CVST patients tends to increase above normal value. D-dimer level have correlation with onset of symptoms and length of stay in CVST patients.Keywords:Cerebral venous sinus thrombosis, D-dimer level, length of stay, onset of symptomsABSTRAK                          Pendahuluan: Trombosis pada vena serebral (cerebral venous sinus thrombosis/CVST) merupakan salah satu diagnosis dalam bidang cerebrovaskular yang sulit ditegakkan karena keterbatasan alat untuk diagnosis pasti. Salah satu faktor risiko terjadinya CVST adalah kelainan koagulasi yang dapat dilihat dari kadar D-dimer yang cenderung meningkat.Tujuan: Mengetahui gambaran profil D-dimer pada penderita CVST dan hubungannya dengan awitan gejala dan lama perawatan di RSUP Dr. Hasan Sadikin, Bandung.Metode: Penelitian ini merupakan penelitian potong lintang. Kriteria inklusi yaitu pasien yang terdiagnosis CVST melalui pemeriksaan digital substraction angiography (DSA) atau computed tomography angiography (CTA) atau magnetic resonance angiography (MRA) dan memiliki profil koagulasi serta dirawat di RSUP Dr. Hasan Sadikin, Bandung pada periode Januari 2018–Mei 2019. Kriteria eksklusi yaitu pasien yang disertai infeksi atau sepsis. Data diambil dari penelusuran rekam medis pasien dan dianalisis menggunakan korelasi Spearman. Signifikansi dinyatakan bila p<0,05.Hasil: Terdapat 40 pasien CVST yang memenuhi kriteria inklusi. CVST mayoritas terjadi pada perempuan (80%), rerata usia 40,75 tahun dengan keluhan utama tersering adalah nyeri kepala (70%). Terdapat 28 pasien memiliki kadar D-dimer yang meningkat (70%). Berdasarkan analisis, kadar D-dimer memiliki hubungan negatif dengan awitan gejala pasien (r=0,319, p= 0,045). Kadar D-dimer juga memiliki hubungan dengan lama perawatan (p=0,012).Diskusi: Kadar D-dimer pada penderita CVST cenderung lebih tinggi dari nilai normal. Kadar D-dimer memiliki hubungan dengan awitan gejala dan lama perawatan pasien CVST di rumah sakit.Kata kunci: Awitan gejala, cerebral venous sinus thrombosis, kadar D-dimer, lama perawatan